Process approach teaching intervention towards writing competence - Mallen, Erlinda Verzo; Otero, Marietta Reyes; Ravina, Maria Clara V.,&ecritic/reader.; Baetiong, Lourdes R.,&ecritic/reader member; Manzano, Virgilio U.,&ecritic/reader member; Soria, Robinson C.,&ecritic/reader member (Quezon City College of Education, University of the Philippines Diliman, 2007)
The process writing approach involves writing skills such as prewriting, drafting, revising, and post-writing stages. This study examined the effects of the approach on the writing proficiency of freshmen college students in the computer school specifically those enrolled in computer science and information technology. The participants are 60 students in Communication Arts (English 2). They were categorized as Moderately Proficient Writers and Less Proficient Writers through the use of TOEFL Writing Proficiency Test. It was revealed that the level of writing proficiency of participants was Level 3 Intermediate Writers which means that they can progress to Advanced Level of writing as shown in test scores before and after the study. In sum, the approach gave the participants sufficient activities where they can engage in writing and revising for particular audience with less anxiety and absence of boredom.
"March 2007."
Thesis (Doctor of Philosophy in Education - Language Education)--University of the Philippines, Diliman
Keywords: English language -- Philippines -- Manila Metropolitan Area -- Rhetoric; Communicative competence -- Philippines -- Manila Metropolitan Area